Cytogenetic evaluation of two species of Cynanchum L. (Apocynaceae) from South India: A possible clue to evolution - Kannan B., Neethu; Thoppil, John E. (Phytotaxa, 2018)
The present study evaluates the chromosome count as well as the karyomorphological analysis of two species of Cynanchum L. (Apocynaceae) viz., C. viminale and C. sarcomedium. In order to investigate cytogenetic variation in Cynanchum species, mitotic squash preparation method was employed. Image analysis system and micro-measure software (AutoCad) were used to provide cytogenetic parameter measurements of karyotypes. The two plant species possess the same diploid (2n = 22) and haploid (n = 11) chromosome numbers and they are differentiated by their karyotype formula and quantitative parameters of the karyotypes. The karyotypic formula of C. viminale and C. sarcomedium are 22 nm and 16 nm + 6 nsm (-) respectively. Various karyomorphometric parameters or indices revealed the evolutionary status of the two species as primitive.